Upaya Meningkatkan Minat Belajar Peserta Didik melalui Model Pembelajaran Problem Based Learning di Kelas XI SMK Negeri 1 Susua - Martinus Buulolo (Departement of Mathematics Education, 2024)
This Classroom Action Research (PTK) aims to describe how to increase students' interest in learning through the Problem Based Learning Model in Class XI of SMK Negeri 1 Susua. This type of research is Classroom Action Research (PTK) which consists of 2 cycles. The subjects in this classroom action research (PTK) were Class XI students at SMK Negeri 1 Susua with a total of 20 students. The results of the research showed that in cycle I, the percentage of students' interest in learning questionnaire answers showed that only 17% of students had a high interest in learning, while 37% of students had sufficient interest in learning, while there were 33% of students who had little interest in learning. and 13% of students who have no interest in learning. This means that, after implementing the problem based learning model, the interest in learning of class XI students at SMK Negeri 1 Susua in cycle I experienced an increase in percentage of only 5%. Therefore, researchers continued research in cycle II. The percentage of answers to the student interest in learning questionnaire obtained was that 72% of students had a high interest in learning, while 18% of students had sufficient interest in learning, while there were 8% of students who had little interest in learning and only 2% of students who have no interest in studying. So it can be concluded that in the cycle there was a significant increase in interest in learning in class XI of SMK Negeri 1 Susua, showing that 90% of students were interested in learning. This shows that the application of the problem based learning model with the improvements made after implementing cycle I has increased. In this case, the problem based learning model can increase students' interest in learning mathematics on the subject of matrix equations (addition and subtraction of matrices) and determining the equation of a circle centered at (0,0) and (a,b) with radius r in class XI of SMK Negeri 1 Susua.